Hysteretic phenomena in Xe-doped C60 from x-ray diffraction - Prokhvatilov, A.I.; Galtsov, N.N.; Legchenkova, I.V.; Strzhemechny, M. A.; Cassidy, D.; Gadd, G.E.; Moricca, S.; Sundqvist, B.; Aksenova, N.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
Polycrystalline fullerite C60 intercalated with Xe atoms at 575 K and a pressure of 200 MPa was studied by powder x-ray diffraction. The integrated intensities of a few brighter reflections have been utilized to evaluate the occupancy of the octahedral interstitial sites in C60 crystals, which turned out to be (34±4) %, and in good agreement with another independent estimate. It is found that reflections of the (h00) type become observable in Xe-doped C60. The presence of xenon in the octahedral sites affects both the orientational phase transition as well as the glassification process, decreasing both characteristic temperatures as well as smearing the phase transition over a greater temperature range. Considerable hysteretic phenomena have been observed close to the phase transition and the glassification temperature. The signs of the two hysteresis loops are opposite. There is reliable evidence that at lowest temperatures studied the thermal expansion of the doped crystal is negative under cool-down.